Brexit disruption and transborder leadership in Europe. Issue 9 (2nd September 2021) - Gibney, John; Liddle, Joyce; Shutt, John
ABSTRACT: The turbulence of Brexit threatens to undermine England–European Union (EU) transborder cooperation at the subnational scale. This paper discusses the lived experience of city and regional leaders involved in developing cross-European cooperation during the early phase of the Brexit 'project'. It contributes to the idea of relational leadership as a framing device for studying leadership in transborder cooperation in the England–EU subnational setting, and surfaces challenges faced by subnational leaders in transborder cooperation during significant policy turbulence. Two main findings of the research have wider relevance for emerging city and regional (place) leadership theory and practice. First, the unanticipated shock caused by Brexit to the supra-national policy environment is impacting significantly on subnational leaders' ability to maintain good transborder working relationships; and second, continuing non-prejudicial dialogue and meaningful conversations between subnational partners are an antidote to the negative legacies of such policy disruption.